The effect of artificial mycorrhization on the growth and development of plants in a vegetation experiment - Vinnikova, O.I. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2024)
Nowadays, numerous commercially available biological preparations based on arbuscular mycorrhizal (AM) fungi are suggested for practical use in agriculture. The potential benefits of inoculating soils with AM fingi for crop production have been shown in many studies. However, the level of the universality of such preparations, i.e. the effectiveness of artificial mycorrhization using one particular fungi species for different agricultural plants, still remains unclear. The aim of present study was to assess the possibility and effectiveness of artificial mycorrhization of tomatoes and wheat under in a vegetation experiment. The effects of adding preparation Mycoplant, which contains propagules of endomycorrhizal fungi, to the soil on seed germination, plant morphometric parameters, and the concentration of chlorophyll in wheat and tomato leaves were assessed. Seeds of wheat lines isogenic for Vrn genes of the Myronivska 808 variety and two varieties of tomatoes - the early-ripening Kremenchutsky rannij variety and the late-ripening Ace variety were used in the experiment. The use of Mycoplant stimulated the germination of wheat seeds: the wheat plants sprouted earlier and moved through the consequent stages of development earlier than in control.  However, an opposite effect took place on the germination of tomato seeds. The treatment with Mycoplant caused an overall tendency to increase of morphometric parameters in wheat isogenic lines Vrn-A1a and Vrn-D1a at different stages of plant growth and development; that correlated with the formation of surface mycorrhiza on the roots. The positive effect of artificial mycorrhization on the photosynthesis was established only for the isogenic line Vrn-D1a, and only at the stage of grain filling. In tomatoes the formation of arbuscular mycorrhiza due to Mycoplant treatment was observed, but no positive effect on the morphometric parameters or chlorophyll concentration in leaves was detected. The maximum frequency of occurrence of mycorrhiza was found in tomatoes of the Kremenchugskii rannijy variety, and the maximum intensity of mycorrhizal formation was found in experimental series of the late-ripening Ace variety.